2019
DOI: 10.1101/688705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of human Brucellosis and associated risk factors among high risk occupations in Mbeya Region of Tanzania

Abstract: 14Background 15 Brucellosis is an infectious zoonotic disease that affects humans, livestock and wildlife. 16 Methods 17 A cross-sectional study was conducted in Mbeya region between November 2015 and January 18 2016 to investigate the seroprevalence of human brucellosis and identify associated risk factors 19 among individuals in risky occupations in Mbeya Region. A total of 425 humans from six 20 occupational categories were serially tested for Brucella antibodies using the Rose Bengal Plate 2 21Test (RBP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Consequently, this increases their exposure to brucellosis. This links in with prevalence studies conducted in Tanzania and Kenya, where men were reported to have a higher seroprevalence for brucellosis than women [52,53]. The differential role that age and gender play in transmission and infection with zoonotic disease is well established and is attributed to the different roles in livestock keeping [19,36,54,55].…”
Section: Culturally Acceptable Behavior Risking Transmission Of Brucellosismentioning
confidence: 68%
“…Consequently, this increases their exposure to brucellosis. This links in with prevalence studies conducted in Tanzania and Kenya, where men were reported to have a higher seroprevalence for brucellosis than women [52,53]. The differential role that age and gender play in transmission and infection with zoonotic disease is well established and is attributed to the different roles in livestock keeping [19,36,54,55].…”
Section: Culturally Acceptable Behavior Risking Transmission Of Brucellosismentioning
confidence: 68%